Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Step-by-step explanation:
12 - 2u = 9u + 45
-2u - 9u = 45 -12
-11u = 33 we'll cut 33 by 11 in 3 times
u = -3 answer
Answer:
u = -3
Step-by-step explanation:
12 - 2u = 9u + 45
12 - 2u + 2u = 9u + 2u + 45
12 = 11u + 45
12 - 45 = 11u + 45 - 45
-33 = 11u
-33/11 = u
-3 = u
Check:
12 - 2(-3) = 9(-3) + 45
12 + 6 = -27 + 45 = 18
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.